CONTROLLING THE IMPLEMENTATION PRUDENTIAL PRINCIPLES IN BANKING LANDING BY FINANCIAL SERVICES AUTHORITY - Zaini, Zulfi Diane; Hakim, Lukmanul (Tadulako Law Review, 2018)
Sources of collection of banking funds collected from the community are then distributed to the community in the form of credit. If the amount of funds disbursed by the bank to the community through credit are not refundable in accordance with the term has been agreed, the credit quality can be classified as non-performing loans or often referred to as Non Performing Loan (NPL). The impact of high NPL levels is disrupted by the liquidity of each banking institution.Research Objectives are: (1) To analyze the supervision of the application of prudential principles in the provision of bank credit conducted by the Financial Services Authority under the Act Number 21 of 2011 on the Financial Services Authority. (2) To analyze the inhibiting factors in supervising the application of prudential principles in the provision of bank credit by the Financial Services Authority. Furthermore, this research uses research method with normative juridical approach, that is by collecting secondary data that is literature materials, as a technique to get information through tracing legislation and other regulations in accordance with research problems and then the data is analyzed by qualitative juridical .The results of the research show that (1) Supervision of prudential principles in the provision of bank credit conducted by the Financial Services Authority under the  Act Number 21 of 2011 concerning Financial Services Authority shall be conducted by Compliance Based Supervision (CBS), that is Compliance Monitoring banks against provisions relating to the operation and management of banks in the past in order to ensure that the bank has been operating and managed properly and properly according to prudential principles. In addition, Risk Based Supervision (RBS) is implemented, ie supervision using risk-based strategies and methodologies that enable bank supervisors to detect significant risks early and take appropriate and timely monitoring actions. (2) Inhibiting factors in supervising the application of prudential principles in the provision of bank credit conducted by the Financial Services Authority is one of the most important that customers often in providing data to the Bank inaccurate and the existence of the prospective customer's delay in completing the file submission of credit.  Keywords:  Supervision, Financial Services Authority, Prudential Banking  Principles, Credit